Analysis of b-Value and Peak Ground Acceleration (PGA) in West Sumatra Province using Maximum Likelihood Method and Empirical Formula (Earthquake data Period 2007-2020) - Fandu Alfadilah; - Syafriani; - Hamdi; Letmi Dwiridal; Fajri Syukur Rahmatullah (Department of Physics – Universitas Negeri Padang UNP, 2022)
West Sumatra Province has four active fault segments, namely part of the Sumatran fault zone which causes frequent earthquakes. Therefore, it is necessary to research b-value analysis and PGA in the province of West Sumatra by using the maximum likelihood method and empirical formula for earthquake disaster mitigation efforts. This study aims to determine the b-value associated with rock stress and PGA as the level of earthquake activity and analyze the distribution map. The data used is earthquake data for the period 2007-2020 with a magnitude ≥ 5 SR and a depth of ≤ 100 km. The results of data processing produce a map of the distribution of b-value and PGA in the province of West Sumatra. The b-value in each region ranged from 0.8421-1.4477. Based on the b-value distribution map, the area that has the smallest b-value is in region 6, while the largest value is in region 2. A low b-value correlates with high rock stress conditions. This value illustrates that area 6 has a high chance of a major earthquake occurring. Furthermore, the calculation of the PGA value refers to the general form of Lin and Wu's empirical equation to obtain a new empirical formula model. The value of the coefficient a=−1.20543, b=−0.839093, and c=6.88858. The PGA value of West Sumatra province ranges from 10.87-376.98 gal. The city/regency with the largest PGA value is in the Mentawai Islands Regency, which ranges from 84.11-328.17 gal and the lowest value is in Dharmasraya Regency, which is between 10.87-35.28 gal.